Preclinical pharmacological profile of Eberconazole: A review and update - Latha Subramanya Moodahadu; Ashis Patnaik; Vakati Venkat Arvind; Ranjit Madhukar Bhide; Kavitha Katta; Binny Krishnankutty; Shantala Bellary (Wolters Kluwer Medknow Publications, 2014)
Eberconazole is a broad-spectrum imidazole antifungal agent used as a topical preparation in the management of cutaneous mycoses. In vitro studies have shown that eberconazole is effective against dermatophytes, candidiasis, yeasts (including those which are triazole resistant) and Pityriasis versicolor. It inhibits fungal lanosterol 14α-demethylase, thereby inhibiting ergosterol synthesis leading to inhibition of fungal growth. In addition to its antifungal activity, it is also effective against Gram-positive bacteria, a property that is useful clinically. It also possesses anti-inflammatory property thus making it a suitable agent in the clinical management of inflamed cutaneous mycoses. Topical application of eberconazole was well tolerated in preclinical studies without any report of delayed hypersensitivity or photosensitivity reactions. There were no phototoxic effects. There was no significant systemic absorption. Animal toxicity studies have shown that it is safe, and the No Observed Effect Level was 2 ml/kg body weight in tested animals. It was not mutagenic and shared similar cytotoxicity profile with other imidazole antifungal products studied. Penetration studies using synthetic membranes revealed that eberconazole intrasets showed less variation as compared to clotrimazole and terbinafine intrasets. Overall amount of eberconazole released was more compared to comparators. In vitro and preclinical studies have demonstrated better therapeutic efficacy with eberconazole than clotrimazole and ketoconazole.